Roles of Additives to Stabilize Lubricated Rolling–Sliding Contacts. Issue 1 (2nd January 2021) - Iwai, Toshiaki; Nakano, Ken
Abstract: Chain continuously variable transmissions (CVTs) are attracting attention as the next-generation practical application and utilize lubricated rolling–sliding contacts for transmitting the engine power. However, their flexible structure sometimes causes vibration and noise problems that need to be solved. In this study, friction tests were conducted for a rolling–sliding contact lubricated by test lubricants with or without two types of additives (i.e., oleylamine as a friction modifier and tricresyl phosphate as an extreme pressure agent) that are typically used for chain CVT fluids. Based on the minimal model of lubricated rolling–sliding contacts, stability analysis was conducted to understand the preferable friction characteristics to prevent vibration and noise problems under the assumption that the friction force is a function of the instantaneous entrainment speed and the instantaneous slide-to-roll ratio. Consequently, it was found that the combined use of oleylamine and tricresyl phosphate is promising, not only because they provide low friction in the boundary lubrication regime but also because they provide adequately rough surfaces that increase the lower limit speed of the hydrodynamic lubrication regime through the mutual inhibitory effects between them.